Extent of compliance of owners : operators of boarding houses and dormitories to the provisions of the city ordinances regulating their operations in the City of Batac, Philippines - Harrison, Michiel Torres (Laoag City : [s.n.], 2019)
This research determined the Extent of Compliance of Owners/Operators of Boarding Houses and Dormitories to the Provisions of City Ordinances Regulating Their Operations in the City of Batac, Philippines. The research followed the descriptive-correlation type of research utilizing a questionnaire to gather data. The 62 owners/operators, and 286 boarders/tenants were taken as respondents.
Bibliography: pages 69-72.
CHED-La Union
Keywords: Ordinances